Social Capital sebagai Mediator antara Trust dan Knowledge Sharing Studi Empiris di Minimarket - Sri Raharso (Universitas Kristen Maranatha, 2016)
The objective of this study is to identify the relation between trust, social capital, and knowledge sharing of mini market employee in Bandung. Employee have to depend on trust in their cooperative activities to justify their expected benefits from the knowledge sharing. Hence, cooperative act as mediator between trust and knowledge sharing. Knowledge sharing is an activity through which knowledge (namely, information, skills, or expertise) is exchanged among people, friends, families, communities or organizations; they are social processedfacilitated by social capital. The results of the analysis highlight significance relationship between trust – knowledge sharing and trust – knowledge sharing via social capital as mediator. As a result, trust is highly overrated as a main driver of knowledge sharing. Hence, social capital plays important role in knowledge sharing process, not trust.Keywords: trust, social capital, knowledge sharing